The Comparison of Atropine & Atropine + Oxime in Organophosphate Poisoning with Muscarinic Signs - Saeed Afzali (پزشکی بالینی ابن سینا, 2002)
Organophosphate insecticides are the choice group  of all  insecticides, now, and are the most  common cause of poisoning. Organophosphates inhibit acetyl –choline esteras enzyme,specialy in parasympatic synapsies in man,and cause muscarinic effects,they also act on somatic nerves and autonomic gangelia to present nicotinic effects, and C.N.S manifestation may also be demonstrated. Drug treatment in these patients include atropine & oximes specially if nicotinic effects are   apparant,oximes will be necessary. This investigation compares two different sorts of treatment as Atropine & Atropine + Oxime in poisoned patient with organophosphates showing muscarinic signs and symptoms.